Review of Chemical Properties and Ethnomedicinal uses of Acanthosicyos horridus Welw. ex Hook. f.: An Indigenous Melon Species of South-West Coast of Africa - Alfred Maroyi, (Journal of Pharmacy and Nutrition Sciences, 2020)
Acanthosicyos horridus Welw. ex Hook. f. is a perennial shrub collected from the wild for its edible fruits and is also used as a traditional medicine. This study is aimed at evaluating the chemical properties and ethnomedicinal uses of A. horridus. Results of the current study are based on data derived from several online databases such as Scopus, Google Scholar, PubMed and Science Direct, and pre-electronic sources such as scientific publications, books, dissertations, book chapters and journal articles. This study revealed that the fruit and root infusions and/or decoctions of A. horridus are used as traditional medicine for arteriosclerosis, chest pains, gastro-intestinal disorders, kidney problems, nausea and sexually transmitted infections. Phytochemical compounds identified from the species include cucurbitacins, fatty acids and sterols. Some of the compounds identified from the species have applications in food industry and health promoting products.